Effect of owner-manager's financial literacy on the performance of SMEs in the Cape Coast Metropolis in Ghana - Daniel Agyapong; Albert Bampo Attram (Journal of Global Entrepreneurship Research, 2019)
Financial literacy enables owner-managers of SMEs to understand and assess their own financial needs and make rational financial decisions. The paper explores the financial literacy of owner-managers of SMEs in the Cape Coast Metropolis and how such literacy influences the performance of their businesses. The study population were owner-managers of registered SMEs in the Cape Coast Metropolis from the National Board for Small and Medium Enterprise, out of which a sample of 132 was selected through the simple random sampling technique. The data was analyzed using Structural Equation Model. The results showed a positive relationship between financial literacy and the firm's financial performance (t~= 35.631, p~< .00). The paper recommends that policy makers should specifically design a program and platform targeted at further enhancing the financial literacy level of these owner-managers to help improve the performance of their firms.
Keywords: 650; Financial literacy; SME performance; Structural equation modeling